KARAKTERISTIK LONCAT HIDRAULIS BEROMBAK DI HILIR PINTU SORONG - , KOMANG ARYA UTAMA; , Dr. Ir. Bambang Yulistiyanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Hydraulic jump is a phenomenon that occurs due to sudden changes in the flow of supercritical flow to subcritical flow. Undular hydraulic jump is a hydraulic jump with a low Froude number which is marked by the emergence of a fixed roller. Information about the characteristics of undular hydraulic jump is still very poor. In order for the interests of the development of science, it is necessary to in-depth study of the hydraulic characteristics and phenomenon that appear on the undular hydraulic jump. This research is applying the 2D physical model that used a tilting flume. Sluice gate is used as a tool to generate the undular hydraulic jump. Measurement of distance and depth using a point gauge and mica ruler while the flow velocity was measured using a Nixon Streamflo 422 Currentmeter. Circulation flow is driven by using water pumps with discharge 15 l/s and 30 l/s, while the volumetric tub is used to calibrate the actual discharge flow for each model experiment. The results of this study indicate that the maximum flow velocity of dimensionless velocity distribution are at 0.5 - 0.9. Lowest value of Froude number obtained in running model Q9A1 is Fr1 = 1.197 and highest value of Froude number obtained in running model Q3A1 is Fr1 limit = 2.258. Due to the less capability of velocity device and the uncomprehensive of measurement, the Coriolis coefficient (ï¡) = 0.94 -1.11 and the Boussiniesq coefficient (Î²) = 0.89 - 1.20. The wave steepness is mild with a slope range are 0.1 to 0.3 or 10% to 30%. The length and height of the wave form are reduce at the first, second, third and so on until the condition of conjugate depth (y3). The Energy loss occurs with the value ïE = 0.03 to 1.039 cm or 0,3% - 10,3%. For more information, the phenomenon of recirculation and flow separation are formed under of the first crest and near of the channel bed. The significant difference value of point velocity gradient near the channel bed between the wave crest to wave trough raises the potential for scouring beneath the wave trough for the mobile bed channel.